2013
DOI: 10.5607/en.2013.22.3.173
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Basis of Optimism and Pessimism

Abstract: Our survival and wellness require a balance between optimism and pessimism. Undue pessimism makes life miserable; however, excessive optimism can lead to dangerously risky behaviors. A review and synthesis of the literature on the neurophysiology subserving these two worldviews suggests that optimism and pessimism are differentially associated with the two cerebral hemispheres. High self-esteem, a cheerful attitude that tends to look at the positive aspects of a given situation, as well as an optimistic belief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 283 publications
3
70
1
5
Order By: Relevance
“…Surprisingly, difficulties regulating negative emotions were also associated with increased FA in the left ATR. The left hemisphere has been primarily associated with the approach of positive stimuli, which will likely elicit positive emotions, while the right hemisphere is more involved in inhibiting actions that may lead to negative emotions . As episodes of elated and depressed mood characterize BD, one might speculate that this lateralization might play a role in the switches between mood states.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, difficulties regulating negative emotions were also associated with increased FA in the left ATR. The left hemisphere has been primarily associated with the approach of positive stimuli, which will likely elicit positive emotions, while the right hemisphere is more involved in inhibiting actions that may lead to negative emotions . As episodes of elated and depressed mood characterize BD, one might speculate that this lateralization might play a role in the switches between mood states.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that only right OFC but not left OFC was associated with trait optimism. A longstanding literature has suggested dichotomous lateralization in the PFC as a function of either approach/avoidance motivation or emotional valence, with the left PFC being related to approach tendency and positive affect, and the right PFC to avoidance tendency and negative affect (e.g., Harmon‐Jones, Gable, & Peterson, ; Hecht, ; Heller, Nitschke, & Miller, ). However, the findings from many recent studies are inconsistent with this traditional hypothesis (see Miller et al, , a systematic review).…”
Section: Discussionmentioning
confidence: 99%
“…This is indirectly related to reduce vigilance against threatening stimuli which help in relieving the symptoms of depression [11]. Furthermore, psychological characteristics such as high self-esteem, the ability of looking at the positive aspects of incidents, as well as an optimistic belief in a bright future are associated with physiological activity in the left-hemisphere (LH) [40], which is hypoactive in depressed patients.…”
Section: Neurological Datamentioning
confidence: 99%